PEMBERIAN INFORMASI MENGENAI PENCEGAHAN PENULARAN PENYAKIT SCABIES DENGAN PERILAKU HIDUP BERSIH DAN SEHAT - Nasution, Nurul Hidayah; Harahap, Yanna Wari (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Scabies is a skin disease caused by Sercoptes scabiei Var humanis. This mite is an obligate parasite for humans. The spread of scabies generally occurs through direct contact between the skin or through sleeping utensils, clothes and towels (Wibisono, 2011). Scabies is often found in Indonesia, this is because Indonesia is a tropical country. This type of service is health promotion with counseling methods. The service was carried out at the Class II B Correctional Institution, Padangsidimpuan City. The population and sample of this service are prison residents with a total of 40 people. The results of this community service were enthusiastically received by prison residents as seen from the many prison inmates who asked questions about how to prevent the spread of scabies which met the requirements for use in everyday life. which can be seen from the number of prison inmates who ask questions about how to prevent the transmission of scabies which meet the requirements for use in everyday life. It is recommended that health educator activities regarding the prevention of transmission of scabies with a clean and healthy lifestyle in the Class IIB Prison in Padangsidimpuan City can be carried out periodically with a more frequent frequency and the range of information dissemination can also be expanded so that it covers all prisoners in general so that prison residents and guards better know, understand and be able to practice the application of prevention of scabies transmission with a clean and healthy lifestyle that meets health requirements in everyday life which in turn can improve the public health status.